1992
DOI: 10.3109/00952999209001609
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Cocaine Abusers in Outpatient Psychotherapy

Abstract: Retention in outpatient psychotherapy of 148 crack and cocaine abusers was examined. The clients were predominantly Black (63%) and Hispanic (21%), predominantly male (87%), and the majority (66%) had completed no more than 12 years of high school. Clients entered treatment in a low-cost treatment center in New York City between June 1987 and November 1988. Forty-two percent (62) of the subjects were seen for one or two research interviews only, and did not return to begin therapy. Of the 86 persons who came t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 27 publications
2
40
1
2
Order By: Relevance
“…Two studies found that retention was better for depressed clients (Martinez-Raga et al 2002;Gerra et al 2006) and three others found that depression was related to dropout (Kleinman et al 1992;Kokkevi et al 1998;Curran et al 2002). However, Curran et al's study makes a useful distinction between severity of depression: whilst severe depression was related to treatment tenure, mild depression was not.…”
Section: Depressionmentioning
confidence: 97%
“…Two studies found that retention was better for depressed clients (Martinez-Raga et al 2002;Gerra et al 2006) and three others found that depression was related to dropout (Kleinman et al 1992;Kokkevi et al 1998;Curran et al 2002). However, Curran et al's study makes a useful distinction between severity of depression: whilst severe depression was related to treatment tenure, mild depression was not.…”
Section: Depressionmentioning
confidence: 97%
“…Quinn et al (1996) and Brandon et al (2003) found smoking severity to be significantly related to early lapse among smokers. Additionally, previous work has implicated substance use severity in substance abuse treatment dropout (Kleinman et al, 1992;Stark, 1992). Thus, individuals with more severe levels of substance dependence may have experienced greater difficulty with both the challenge tasks and remaining in treatment due to the long-term effects of more severe substance abuse (e.g., neurological, psychological; Saunders & Brady, 2002).…”
Section: Predictors Of Treatment Dropoutmentioning
confidence: 99%
“…However, a number of studies have reported no association between age and the likelihood of completing treatment (Claus, Kindleberger, & Dugan, 2002;Robinson & Little, 1982), making it difficult to draw definitive conclusions regarding age and treatment dropout. Race/ethnicity While some studies have reported that race has little effect on treatment dropout (McFarlain, Cohen, Yoder, & Guidry, 1977;Raynes & Patch, 1973;Sells, Chatham, & Joe, 1972), it has been suggested that Caucasians have higher completion rates than African Americans and Hispanics (Kleinman, Kang, Lipton, & Woody, 1992). In the majority of studies reporting differences in race/ethnicity, the role of race/ethnicity in dropout is not a primary aim, making it unclear from the results that these differences were not confounded by age, employment levels, or education levels.…”
Section: Demographic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Clinicians at the authors' therapeutic community observed that cocaine-dependent women drop out of treatment early, often stating that their children need them at home. Unfortunately, these early dropouts too often relapse to cocaine use with disastrous consequences for themselves and their children.…”
Section: Introdutionmentioning
confidence: 99%